2008
DOI: 10.1534/genetics.107.081166
|View full text |Cite
|
Sign up to set email alerts
|

The Fixation of Locally Beneficial Alleles in a Metapopulation

Abstract: Extinction, recolonization, and local adaption are common in natural spatially structured populations. Understanding their effect upon genetic variation is important for systems such as genetically modified organism management or avoidance of drug resistance. Theoretical studies on the effect of extinction and recolonization upon genetic variance started appearing in the 1970s, but the role of local adaption still has no good theoretical basis. Here we develop a model of a haploid species in a metapopulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Our results are consistent with previous results for discrete demes. When discrete demes (or metapopulations) experience heterogeneous selection, low migration rates favour establishment of a new mutation (Nagylaki 1980; Tachida & Iizuka, 1991; Gavrilets & Gibson, 2002; Whitlock & Gomulkiewicz, 2005; Vuilleumier et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous results for discrete demes. When discrete demes (or metapopulations) experience heterogeneous selection, low migration rates favour establishment of a new mutation (Nagylaki 1980; Tachida & Iizuka, 1991; Gavrilets & Gibson, 2002; Whitlock & Gomulkiewicz, 2005; Vuilleumier et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The main work on this (Whitlock 2003) only describes the probability of fixation of a new mutation, and does not give any approximations for the fixation probability of alleles with a higher frequency. However, it is well known that extinction and recolonization can lead to drastic reductions in the effective population size (Slatkin 1977; Whitlock and Barton 1997; Whitlock 2003; Vuilleumier et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2008). Using a simulation approach, Vuilleumier et al. (2008) showed that this reduction in effective population size indeed leads to a reduction in the probability of fixation of a beneficial allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work has focused on how different aspects of population subdivision affect the fixation probability of an advantageous allele (Patwa & Wahl, 2008), such as extinction and recolonization of demes (Barton, 1993; Whitlock, 2003; Cherry, 2003b, 2004), the impact of selfing and dominance of mutations (Whitlock, 2003; Roze & Rousset, 2003), frequency‐dependent selection (Cherry, 2003a; Pannell et al. , 2005), and environmental heterogeneity (Lenormand, 2002; Whitlock & Gomulkiewicz, 2005; Vuilleumier et al. , 2008).…”
Section: Introductionmentioning
confidence: 99%